(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In this research work, the effect of Tungsten-doping on the crystal structure, morphology and antimicrobial of titanium dioxide nanoparticles were studied. The pure and different weight % of tungsten doped TiO2 nanoparticles were synthesized by sol–gel method and calcinated at 600°C for 5 hours. The synthesised products have been characterized by X-ray Diffraction studies (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), Elemental analysis (EDXA), Ultra Violet Visible Spectroscopy (UV-Vis), Photoluminescence Spectra (PL), High Resolution Transmission Spectroscopy (HRTEM) and Fourier Transform Infra Red Spectroscopy (FT-IR). XRD pattern of pure TiO2 and 1 weight % W-doped TiO2nanoparticles confirms the anatase structure and increase in the W-doping changes the phase of TiO2 to rutile. Average crystallite size of synthesized nanoparticles was determined using the Debye–Scherrer formula. The crystallite size obtained for pure TiO2 is in the range from 29 nm to 39 nm and W-doped TiO2 is varied from 28 to 34 nm. The SEM images show the agglomerated particles of spherical-like morphology. Optical property and direct bandgap of pure and W-doped TiO2nanoparticles also further characterised by UV–Vis Spectroscopy. The images of HRTEM clearly confirm that particles present in the W-doped TiO2 powdered sample is nanosized particles. The Kirby Bauer Agar Well Diffusion Assay method was employed to explore antimicrobial activity of nanosized pure and W-doped TiO2 colloidal suspension against the test microorganisms two Gram positive bacteria(Staphylococcus aureus, Bacillus subtilis),two Gram negative Bacteria(Escherichia coli, Pseudomonas aeruginosa),and two fungi(Candida albicans, Aspergillus niger). It shows that the W- doped TiO2 nanoparticles inhibited the multiplication and growth of the above mentioned test bacteria and fungi. Antimicrobial activity was found against all tested microorganisms which confirmed that W-doped TiO2 nanoparticles possess high antimicrobial activity compared to pure TiO2 nanoparticles.